PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVB SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Elvira Susanti; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the students achievement of science lessons at SDN 023 Sedinginan fourth B graders still low with an average of 61,25 and minimum completeness criteria (KKM) science lessons is 70. Between students, amounting to 20 people only 12 students who achieve classical KKM with 60,00%. This research is Classroom Action Reseach (CAR), which aims to improve the student achievement of science lessons class IVB at SDN 023 Sedinginan with implementation cooperative learning model type Numbered Head Together (NHT). Formulation of problem: is the implementation of cooperative learning model type Numbered Head Together(NHT) can improve students achievement of science studies at SDN 005 Sedinginan. The research was conducted on April to Mayl, 2016 by 2 cycles. Subjects were students of SDN 023 Sedinginan, total 20 people who use data source. The data collection instruments this thesis is a teacher and students activities sheets and students achievement. This thesis presents the result obtained each day before the action an improve in base score cycle with the average being 61,25. In the first cycle improve an average of 72,5 with increase big as 18,36% and improve in the second with an average of 81,00 with incrase big as 32,24 %. Activities of the teacher in the learning process in cycle of 22,91% with incease big as 64,58% and the second meeting improve to 87,49. Result of data analysis of students activities in the first cycle with the first meeting of an average of 22,91% with incease big as 64,58% and the second meeting improve to 87,49. The and classical increase for 40% increase to 30% for 70% at the firt cycle, next increase 5% to 95% in second cycle. The result in research can conclution in the class IVB at SDN 023 Sedinginan that the implementation of cooperative learning model of Numbered Head Together (NHT) can improve student achievement of science lessons at fourth B graders SDN 023 Sedinginan. Key words: Kooperative Learning, Numbered Head Together, Result Of Science Studies